Tantangan Guru Akidah Akhlak dalam Mengintegrasikan Nilai-Nilai Islam di Era Globalisasi pada Siswa Madrasah Ibtidaiyah (MI) DDI Mangempang Kecamatan Barru Kabupaten Barru - Haslinda; Rusman (PT. Hasba Edukasi Mandiri, 2025)
This research aims to examine the challenges encountered by Aqidah Akhlak teachers in integrating Islamic values within the dynamics of globalization and to identify innovative strategies that can enhance both the learning process and the application of Islamic principles in contemporary education. Using a descriptive qualitative method, the data were obtained through observation, interviews, and documentation. The results indicate that teachers face several obstacles, including the influence of global culture that often contradicts Islamic teachings, the uncontrolled spread of information, and the decline of moral values among students. However, Aqidah Akhlak teachers are able to transform these challenges into opportunities by developing creative learning approaches and employing technology prudently. With the implementation of effective strategies, Islamic education can play a vital role in shaping a generation that excels intellectually, remains spiritually grounded, and possesses strong moral integrity.